Constraint-induced movement therapy for lower extremity use in activities of daily living in people with chronic hemiparesis: multiple case study - Duarte Pereira N. (2022)
© 2022 Lippincott Williams and Wilkins. All rights reserved.Lower extremity constraint-induced movement therapy (LE-CIMT) is an intensive intervention protocol recently reported to improve lower extremity use in individuals with chronic hemiparesis. To test if the LE-CIMT that uses essential CIMT components, including the transfer package and intensive task-oriented training, is a feasible and potentially effective intervention to improve the lower extremity real-world use and functional ability in a group of individuals with chronic hemiparesis. A quasi-experimental pre- and post-test design study with 12 individuals with chronic stroke and impaired ambulation skills engaged in a 10-weekday LE-CIMT. Intervention feasibility was assessed, examining the training adherence, acceptability, and safety. The lower extremity motor activity log (LE-MAL), lower extremity motor function test (LE-MFT), timed up and go (TUG) and spatiotemporal gait parameters were used as clinical outcomes. Clinical data were collected at baseline, 3-day post-CIMT protocol and 30-day follow-up assessment. At baseline, LE-MAL and LE-MFT outcomes were tested over 2-week apart to ensure a stable measurement and determine the smallest real difference (SRD) in the study sample. The LE-CIMT showed excellent adherence, acceptability and safety. Ten out of 12 participants showed improvements over SRD in LE-MAL composite score (1.2 point) and eight participants in LE-MFT adjusted scores (0.8 point) in post-CIMT and 30-day follow-ups. LE-CIMT is a feasible intervention that has the potential to promote improvements in real-world use and functional ability of the paretic lower extremity in individuals with chronic stroke.